Improved cryopreservation method for the long-term conservation of the world potato germplasm collection - Panta, A.; Panis, Bartholomeus; Ynouye, C.; Swennen, Rony L.; Roca, W.; Tay, D.; Ellis, David (Springer, 2015)
The effect of cold and sucrose pretreatment for increasing tolerance to cryopreservation was evaluated with eight diverse genotypes, six cultivars belonging to the cultivated species, Solanum tuberosum spp., S. tuberosum subsp. andigena, S. x juzepczukii and S. x ajanhuiri, and two genotypes from the wild species, S. commersonii. In vitro plantlets were cultured at either 6 or 22 °C in media supplemented with either 0.07 or 0.3 M sucrose prior to droplet PVS2 cryopreservation. The sucrose pretreatment appeared to have no positive effect on post-cryo survival. The cold-hardening pretreatment increased significantly post-cryo recovery in drought and frost tolerant cultivars. When 755 accessions, representing 10 taxa, were cryopreserved after cold-hardening, 96 % responded with at least one shoot recovering and 63 % showed a high recovery rate (40–100 %). Therefore this method is recommended for the long term conservation of diverse accessions of potato germplasm.